Prevalence, utilization, and costs of antiepileptic drugs for epilepsy in Germany – a nationwide population-based study in children and adults - Hamer, Hajo; Dodel, Richard; Strzelczyk, Adam; Balzer-Geldsetzer, Monika; Reese, Jens-Peter; Schöffski, Oliver; Graf, Wolfgang; Schwab, Stefan; Knake, Susanne; Oertel, Wolfgang; Rosenow, Felix; Kostev, Karel (Journal of Neurology, 2012)
<h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);"> Nationwide analyses of drug use can provide a prevalence estimate of the underlying disease and can help in understanding the characteristics of treatment. This study aimed for such analyses regarding the utilization of antiepileptic drugs (AED) for epilepsy in Germany. In 2009, all 4,115,705 AED prescriptions of all German patients with statutory health insurance (70,011,508 persons) were retrospectively analyzed. The IMS® LRx database served as data source, which accesses nationwide pharmacy data centers processing all German prescription data. To establish the age and sex-specific percentage of patients taking AED because of epilepsy, we used a second database, Disease Analyzer®, which covered a representative sample of the German population (7.2 million patients) and contained ICD10 codes alongside with prescription data. The period prevalence of patients taking AED because of epilepsy was 9.1/1,000 (children/adolescents: 5.2/1,000; elderly: 12.5/1,000). Of the patients, 83.1 % took at least one of four AED: valproate (29.8 %), carbamazepine (26.4 %), lamotrigine (21.4 %), and levetiracetam (16.9 %). Oxcarbazepine and sultiame were popular with pediatricians. Elderly patients frequently received phenytoin and primidone. More than half of the patients were treated by family physicians; 68 % took AED in monotherapy and 7.9 % received >2 AED (children/adolescents: 12.5 %). The costs for AED prescribed for epilepsy amounted to €285.1 Mio (median AED costs/patient: €158/a). The German 2009 prevalence of epileptic patients taking AED was 9.1/1,000. Family physicians cared for the majority of patients. Prevalence and prescribing patterns changed with age. Costs of AED against epilepsy added up to 1 % of total medication costs in Germany.
WiSo-Import:2015-03-26:4184
Keywords: Epilepsy; Prevalence; Antiepileptic drugs; Costs; Children; Elderly